Indícios de representações sociais de professores de matemática sobre o pensamento algébrico de alunos autistas - Ferreira, Maximiliam Albano Hermelino (2022)
This research is inserted in the context of Inclusive Mathematics Education and in the problem of the perceptions that Mathematics teachers have when teaching Algebra to autistic students. The research problem proposed in the form of the guiding question was “What are the signs of social representations of mathematics teachers that we can identify about the development of algebraic thinking in autistic students?”. The qualitative-quantitative research had the general objective of identifying evidence of social representations of Mathematics teachers on the development of algebraic thinking in autistic students. The theoretical framework adopted was the Theory of Social Representations supported by typology and conceptions of algebraic thinking in the perspective of Radford (2006). The methodological axis was assumed to be the Collective Subject Discourse (CSD) method complemented by the use of wordclouds. Data were collected through an online questionnaire directed to Brazilian Mathematics teachers who taught for the Final Years of Elementary School and had, among their students, an autistic student. Data were processed using DSCsoft and NVivo software. Eleven DSC and five wordclouds were obtained. The CSD pointed out that the participants in general agree with the inclusion of students who are the target audience of Special Education in common classrooms as long as the teachers and the school are prepared to receive them, in addition, they consider that their autistic students have difficulties in socialization. The wordclouds showed evidence that the participants in general establish a relationship between algebraic thinking and alphanumeric symbolism, propose activities to autistic students that involve only arithmetic thinking, and provide concrete materials to these students. The conclusions point to the need to train Mathematics teachers both on the diversity of behaviors and cognitive possibilities of autistic students and on different Algebra teaching strategies that allow all students to appropriate more complex forms of algebraic thinking